Therapeutic effects of Cosmos caudatus kunth leaf extract in the prevention and treament of obesity in sprague dawley rats - Abdul Rahman, Hafeedza (2015)
Obesity is a common nutritional disorder that has become one of the most important health issues of modern society around the world. Accumulating studies have shown that various herbs can be good sources of potent antioxidants. However, little information is available on the anti-obesity potential of these herbs. Preliminary study was carried out to investigate the anti-obesity and antioxidant activity of 8 common herbs, namely Cosmos caudatus, Pluchea indica, Lawsonia inermis, Carica papaya, Piper betle, Andrographis paniculata, Pereskia bleo and Melicope lunu. Antiobesity activity was assessed using inhibition of pancreatic lipase (PL) and lipoprotein lipase (LPL) activity whereas antioxidant activity was measured using free radical DPPH (2,2-diphenyl-2-picrylhydrazyl) scavenging activity. Results of the preliminary study revealed that C. caudatus exhibited good anti-obesity activity as well as excellent antioxidant activity. Therefore, C.caudatus was selected for further study by extraction with different concentrations of ethanol (100%, 80%, 60%, 50% and 40%). Hundred percent ethanol extracts of C. caudatus showed highest activity in both anti-obesity (21.8±1.5% and 19.9±1.1% in pancreatic and lipoprotein lipase assay) and antioxidant activity (24.9±1.1 μg/mL) with total phenolic content of 865.8±5.0 mg GAE/g extract and total flavonoid content of 398.8±34.8 mg RE/g extract compared to that of other extracts. Strong positive correlation between antioxidant activity (DPPH) and both phenolic (r =0.708) and flavonoid (r = 0.766) content was observed. The same trend existed between anti-obesity (PL and LPL) and that of phenolic (r = 0.935,0.845) and flavonoid (r = 0.945, 0.835) compounds respectively. The extract consisted of various flavonoids (quercetin, quercitrin, catechin,epicatechin, kaempherol, rutin, and chlorogenic acid) as identified by nuclear magnetic resonance (NMR), liquid chromatography mass spectroscopy (LC-MS), and high performance liquid chromatography (HPLC). Based on the results obtained, 100% ethanol extract of C.caudatus was further assessed for the preventive and therapeutic effects of obesity in vivo. In the preventive study, C. caudatus extract (175 mg/kg and 350 mg/kg body weight) was given to the lean Sprague dawley rats fed with high fat diet (HFD) for 11 weeks whereas in the treatment study, obese rats were treated with C. caudatus extract (200 mg/kg and 400 mg/kg body weight) for 9 weeks. In the preventive study, the extracts significantly suppressed the increase in body weight gain by 33.0 - 42.5% and percentage of abdominal fat by 33.0 - 42.0% when compared to that of control HFD group. However, it failed to reduce the weight and percentage of abdominal fat in HFD induced obese rats. Nevertheless, for both experiments the extract significantly suppressed the increase of plasma triglycerides, total cholesterol, LDL, insulin and leptin level. In addition,plasma ghrelin and adiponectin levels were increased. The extract also increased the fecal excretion of fat in rats (96.9±10.5 - 114.6±9.3 mg/g in preventive study and 87.7±10.0 - 124.6±20.2 mg/g in treatment study) when compared to that of control HFD groups (55.4±6.6 - 58.2±2.6 mg/g) respectively, suggesting that C. caudatus reduces the progression of obesity by inhibiting pancreatic lipase, leading to malabsorption of fat,validating the in-vitro results obtained in first part of the study. In the final part of the study, both urine and serum metabolites of rats were analyzed using (NMR) spectroscopy and multivariate data analysis (MVDA). Lean and obese rats were clearly discriminated from each other on Orthogonal partial least square (OPLS-DA) score plot proving the ability of the high fat diet used in inducing obesity. Metabolites associated with lipid, tricarboxylic acid cycle (TCA), glucose, amino acid, creatine and gut microbiota metabolism were found to be responsible for the discrimination observed. Interestingly, the therapeutic effects of C. caudatus extracts, specifically the low dose (200 mg/kg) were found to be better than that of Orlistat, based on the fact that the metabolic profiles of C. Caudatus treated groups were very similar to that of normal group. Betaine, succinate, 3-hydroxybutyrate,creatine, glycine, N-acetylglycine, pyruvate and glutamine were significantly increased/ decreased towards the normal level. Finally, partial least square analysis (PLS-DA) showed that the obese group moved away from the position of lean group and after 9 weeks of treatment both treated groups were regulated back closer towards their healthy baseline levels,confirming the therapeutic effects of the extracts obtained from biochemical assays measured in the previous chapter. This study showed the antiobesity effects of C. caudatus through inhibition of lipase activity as demonstrated by the increase in fecal fat content and also the positive effects on other obesity biomarkers measured. It also successfully demonstrated the ability of NMR based metabolomics in unraveling therapeutic effects of C. caudatus and further provides biochemical insights into the metabolic alterations associated with obesity. Results of the study suggest that C. caudatus has potential as a natural supplement or functional ingredient for the prevention and treatment of obesity.